Individual, Organizational, and Work Environment Factors Associated with Burnout among Nurses at Sumberglagah Regional Public Hospital - Henry Sudiyanto; Irvan Widodo; Arief Fardiansyah (Universitas Muhammadiyah Sidoarjo, 2025)
Background: Burnout syndrome among nurses is a critical occupational health issue that can impair job performance, reduce patient safety, and increase turnover rates. This study aimed to analyze the influence of individual factors, organizational factors, and work environment on the incidence of burnout syndrome among nurses at Sumberglagah Regional Public Hospital. Method: A cross-sectional design was employed, involving 99 nurses selected through simple random sampling from a total population of 131 nurses. Data were collected using validated questionnaires measuring individual factors, organizational support, work environment quality, and burnout syndrome using the Maslach Burnout Inventory-Human Services Survey (MBI-HSS). Data analysis included univariate, bivariate (Chi-square), and multivariate (multiple linear regression) tests. Result: The results showed that individual factors (p = 0.000, β = –15.763) and work environment (p = 0.000, β = –10.671) had a significant negative effect on burnout syndrome, indicating that higher scores in these areas were associated with lower burnout levels. Organizational factors (p = 0.107, β = –5.667) were not found to have a statistically significant independent effect. Conclusion: These findings highlight the need for integrated interventions combining personal resilience training with improvements in workplace conditions. Strengthening coping skills, fostering positive thinking, ensuring adequate staffing, and providing supportive physical and psychosocial environments are recommended strategies to reduce burnout risk. Implementing such measures is essential for protecting nurse well-being and maintaining the quality and safety of healthcare services.